Підтримка прийняття рішення щодо вибору методу одержання кардинальних експертних оцінок - Totsenko, V. G.; Tsyganok, V. V.; Kachanov, P. T. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The paper shows a method for obtaining cardinal expert estimates should be chosen, which, in the opinion of the decision-making person, corresponds, best of all, the current situation. The choice is based on the application of the experimentally obtained estimates on several criteria of the expert estimation, and determined by indices, defined by decision-making person, of relative significance of these estimates with respect to the specific situation. The choice is done in two stages. At the first stage the Pareto-optimal set of the methods is determined, at the second stage the generalized cardinal estimates of relative efficiency of the methods from the set in question are calculated.